2018
DOI: 10.1177/2168479017738723
|View full text |Cite
|
Sign up to set email alerts
|

Value of Developing Plain Language Summaries of Scientific and Clinical Articles: A Survey of Patients and Physicians

Abstract: Our results indicate PLS could play an important role in the patient-physician dialogue. Although patients in this study tended to be more informed and engaged than the general patient population, with continued expansion of online platforms and open-access publishing, it is likely that greater numbers of patients will seek more specialized health-related information in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…With the increased uptake of online platforms and open-access publishing, it is also likely that more patients will want to access specialized health-related information. 12 Therefore, PLS might in the future, if more ubiquitous, become vehicles that bring together HCPs, researchers, patients, caregivers, and the public.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increased uptake of online platforms and open-access publishing, it is also likely that more patients will want to access specialized health-related information. 12 Therefore, PLS might in the future, if more ubiquitous, become vehicles that bring together HCPs, researchers, patients, caregivers, and the public.…”
Section: Introductionmentioning
confidence: 99%
“…After general internet searches (61%) and patient-specific websites (57%), articles in scientific journals (47%) were the third most important online source of health-related information for patients. 12 Of the physicians who were surveyed, 60% indicated that they would use PLS, with 46% rating PLS as valuable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19]. Other studies have described the development of a plain language support tool for cancer clinical trials or plain language summaries of scientific articles [23,40] and found that this could play an important role in the patient-physician dialogue. However, these studies were merely focused on patient empowerment and not directly on improving communication behavior from healthcare professionals.…”
Section: Plain-language Guide For Breast Cancer Genetic Counseling Anmentioning
confidence: 99%
“…As part of its overarching patient partnering strategy for medicines development [11,13,20], UCB Pharma is now implementing the structured and systematic use of PES. Successful development and deployment of PES in selected studies could give a voice to and benefit many participants around the world.…”
Section: Introductionmentioning
confidence: 99%